Sculpture as Literature and History: Captive and Captivating Venus Figures from the Greek Revolutionary Era - Gonda Van Steen (European Journal of American Studies)
This paper focuses on the sculpture of the Venus de Milo, a chance find of 1820, but a token discovery in the fermentation brought on by the growing tensions between the Ottoman administrative hierarchies, the foreign diplomats, the Greek intellectuals and yet aspiring revolutionaries, and the local populations of the Aegean islands. For lack of an ancient history of the Venus, antiquarianism, treasure-hunting, archival evidence, and Greek revolutionary history blend in the statue’s new lease on life, which is a Western afterlife in literature and legend as well as in history, from which the islanders of Milos have all but been erased. The Venus de Milo has become an iconic figure, heavily overwritten by aesthetic judgments, adventure stories of movement and migration, and the accounts of personal and political trajectories, all playing out in the upper and Western echelons of imperialist Europe and its classist (and racist) underpinnings.